MP-12 virus containing the clone 13 deletion in the NSs gene prevents lethal disease when administered after Rift Valley fever virus infection in hamsters - Gowen, Brian B.; Westover, Jonna B.; Sefing, Eric J.; Bailey, Kevin W.; Nishiyama, Shoko; Wandersee, Luci; Scharton, Dionna; Jung, Kie-Hoon; Ikegami, Tetsuro (Frontiers in Microbiology, 2015)
Rift Valley fever virus (RVFV; Bunyaviridae, Phlebovirus) causes a range of illnesses that include retinitis, fulminant hepatitis, neurologic disease, and hemorrhagic fever. In hospitalized individuals, case fatality rates can be as high as 10–20%. There are no vaccines or antivirals approved for human use to prevent or treat severe RVFV infections. We previously tested the efficacy of the MP-12 vaccine strain and related variants with NSs truncations as a post-exposure prophylaxis in mice infected with wild-type pathogenic RVFV strain ZH501. Post-exposure efficacy of the rMP12-C13type, a recombinant MP-12 vaccine virus which encodes an in-frame truncation removing 69% of the NSs protein, resulted in 30% survival when administering the virus within 30 min of subcutaneous ZH501 challenge in mice, while the parental MP-12 virus conferred no protection by post-exposure vaccination. Here, we demonstrate uniform protection of hamsters by post-exposure vaccination with rMP12-C13type administered 6 h post-ZH501 infection while no efficacy was observed with the parental MP-12 virus. Notably, both the MP-12 and rMP12-C13type viruses were highly effective (100% protection) when administered 21 days prior to challenge. In a subsequent study delaying vaccination until 8, 12, and 24 h post-RVFV exposure, we observed 80, 70, and 30% survival, respectively. Our findings indicate that the rapid protective innate immune response elicited by rMP12-C13type may be due to the truncated NSs protein, suggesting that the resulting functional inactivation of NSs plays an important role in the observed post-exposure efficacy. Taken together, the data demonstrate that post-exposure vaccination with rMP12-C13type is effective in limiting ZH501 replication and associated disease in standard pre-exposure vaccination and post-challenge treatment models of RVFV infection, and suggest an extended post-exposure prophylaxis window beyond that initially observed in mice.